Accountant Skill Gen Z Fresh Graduates in Digital Era: A Systematic Literature Review - Mohammad Iqbal Firdaus; Rizka Furqorina (Jurnal Akuntansi Aktual, 2024)
Purpose: The purpose of this study is to investigate the impact of emerging technologies on the skills required for accountants in the digital era, particularly focusing on the skills needed by Gen Z fresh graduates. Method: The present study builds on a systematic literature review of 41 academic articles published in Scopus Database between 2017 and 2024. It is based on the “preferred reporting items for systematic reviews and meta-analyses” (PRISMA) method. Synthesising research through a transparent, rigorous and replicable process makes it possible to explore and identify accountant skill in digital era. Findings: The findings highlighted the need for accountants to possess digital literacy skills, data analytics skills, and the ability to work collaboratively with professionals from other fields. The study also emphasized the importance of continuous professional development to keep pace with the rapid technological advancements in accounting. Originality/Value: This paper offers a comprehensive literature review on impact of emerging technologies on the skills required for accountants in the digital era, particularly focusing on the skills needed by Gen Z fresh graduates. It could provide a insight and guidance for accounting fresh graduate to possess digital literacy skills, data analytics skills, and soft skills to adapt to technological changes and meet the needs of the dynamic accounting industry.